2014
DOI: 10.1371/journal.pone.0087969
|View full text |Cite
|
Sign up to set email alerts
|

Shifting from Right to Left: The Combined Effect of Elevated CO2 and Temperature on Behavioural Lateralization in a Coral Reef Fish

Abstract: Recent studies have shown that elevated CO2 can affect the behaviour of larval and juvenile fishes. In particular, behavioural lateralization, an expression of brain functional asymmetries, is affected by elevated CO2 in both coral reef and temperate fishes. However, the potentially interacting effects of rising temperatures and CO2 on lateralization are unknown. Here, we tested the combined effect of near-future elevated-CO2 concentrations (930 µatm) and temperature variation on behavioural lateralization of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
52
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 62 publications
(60 citation statements)
references
References 27 publications
(50 reference statements)
6
52
2
Order By: Relevance
“…Hence, exposure to hypoxia might cause right-lateralized individuals to become leftlateralized (see peak at LR=−60), resulting in the loss of the original side bias in the whole population while maintaining a similar individual-level lateralization as in normoxia. A similar effect was found in a coral reef fish, where exposure to elevated CO 2 levels affected population-level but not individual-level lateralization (Domenici et al, 2014). In contrast, studies on other species reported an effect of exposure to elevated CO 2 in individual-level but not in population-level lateralization (e.g.…”
Section: Short Communicationsupporting
confidence: 61%
See 3 more Smart Citations
“…Hence, exposure to hypoxia might cause right-lateralized individuals to become leftlateralized (see peak at LR=−60), resulting in the loss of the original side bias in the whole population while maintaining a similar individual-level lateralization as in normoxia. A similar effect was found in a coral reef fish, where exposure to elevated CO 2 levels affected population-level but not individual-level lateralization (Domenici et al, 2014). In contrast, studies on other species reported an effect of exposure to elevated CO 2 in individual-level but not in population-level lateralization (e.g.…”
Section: Short Communicationsupporting
confidence: 61%
“…Some evidence and theoretical work suggests that stressful situations could cause a shift of information processing between the two hemispheres (i.e. from left to right control) (Rogers, 2010;Domenici et al, 2014). In line with Rogers (Rogers, 2010), it is possible that the stress due to hypoxia caused treated subjects to increase right-hemisphere control.…”
Section: Resultsmentioning
confidence: 84%
See 2 more Smart Citations
“…Indeed, nocturnally active fish species that spend less than 30 days in the pelagic environment before settling have a larger optic tectum and telencephalon than diurnal fish species that spend less than 15 days in the ocean . Additionally, behavioural lateralization in coral reef fish larvae is impaired by ocean acidification (Domenici et al, 2014Nilsson et al, 2012). Few studies have explored whether lateralization could vary across the development of an individual (Concha, Bianco, & Wilson, 2012;Rogers et al, 2013;Skiba, Diekamp, & Güntürkün, 2002).…”
mentioning
confidence: 99%